Pengaruh Dosis Rhizobium Serta Macam Pupuk NPK Terhadap Pertumbuhan Tanaman Kedelai (Glycine max) Varietas Anjasmoro - Arina Manasikana; Lianah kuswanto; Kusrinah Kusrinah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Efforts to increase the growth and yield of soybean plants can be done through the use of cultivation technology, namely by providing biological fertilizer treatments such as N-fixing bacteria, namely Rhizobium. The study aims to determine the effect of the right Rhizobium dose and type of NPK fertilizer on the growth of the Anjasmoro variety of soybean (Glycine max). This research uses a factorial randomized block design with two factors and three repetitions. The first factor is Rhizobium inoculation consisting of I0: No inoculum, I1: Rhizobium inoculum (5 g / kg seed), I2: Rhizobium inoculum (7 g / kg seed), I3: Rhizobium inoculum (9 g / kg seed). The second factor is the type of NPK fertilizer, namely P0: No fertilizer, P1: solid NPK fertilizer (0.8 g / plant), P2: liquid NPK fertilizer. The results showed that the dose of Rhizobium that could affect soybean growth was a dose of 9 grams/kg of seed that significantly affect ed the number of leaves and leaf color but did not significantly affect plant height, number of branches, number of root nodules and root nodules weight. NPK fertilizer that can affect soybean growth is liquid NPK fertilizer, and only has a significant effect on leaf color. The interaction of Rhizobium inoculation treatment and NPK fertilizer types significantly affected most parameters but did not significantly affect the number of branches and weight of root nodules.